Stromal Mystery with Cellular Secrets - Navigating Tumor Terrain: Insights Into Endometrial Tumors - A, Sivaranjani.; B, Shobana.; Lilly, Mary; Sudha, Sai; Prita, Jeev (Journal of Neonatal Surgery, 2025)
Uterine smooth muscle tumors and endometrial stromal tumors (ESTs) are the two major types of mesenchymal tumors of the uterus, the latter being fairly uncommon. Among these, endometrial stromal sarcoma (ESS) accounts for less than 1% of all uterine tumours. Endometrial stromal tumors (ESTs) are rare uterine mesenchymal neoplasms and on occasion pose a diagnostic dilemma for pathologists if it coexists with leiomyomata.[1] According to the current WHO classification, they have been categorized into endometrial stromal nodule, low-grade endometrial stromal sarcoma (LG‑ESS), high‑grade ESS, and undifferentiated uterine sarcoma. Cellular leiomyoma (CL) often simulates EST due to increased cellularity. We hereby report a series of 4 cases which posed a diagnostic challenge to us as all the cases had concurrent leiomyoma along with ESTs. We therefore discuss the histological features of ESTs which helped us resolve this dilemma as well as the utility of immunohistochemistry (IHC) as a diagnostic aid in arriving at a final diagnosis in such problematic cases.